A broad-range temperature sensor dependent on the magnetic and optical properties of SrF2:Yb3+, Ho3+. Issue 9 (12th February 2019) - Du, Shanshan; Wang, Yuhua
Abstract : Co-doped SrF2 : Yb 3+, Ho 3+ nanoparticles (NPs) have been successfully synthesized and upconversion luminescence (UCL) was demonstrated under excitation at 980 nm. Abstract : Co-doped SrF2 :Yb 3+, Ho 3+ nanoparticles (NPs) have been successfully synthesized and upconversion luminescence (UCL) was demonstrated under excitation at 980 nm. The integrated intensity of UC emissions was found to be markedly influenced by the concentration of Yb 3+ and Ho 3+ in the NPs. The optimized doping concentrations of Yb 3+ and Ho 3+ were determined to be 20% and 2%, respectively, to obtain maximum UCL intensities in the range of 500 nm to 800 nm. The phonon energy dependent behavior should essentially reflect the energy transfer excitation mechanism. Furthermore, the abnormal thermal quenching behavior is primarily considered to be induced by defects caused by non-equivalent lanthanide (Ln 3+ ) ions replacing Sr 2+ ions, in that upon an increase in the temperature, the emission intensity peak at 656 nm is relatively thermally stable at first and then decreases, and the emission intensities at 543 and 752 nm decrease gradually at first, and then increase and reach a maximum at 450 K, at which point the emission intensity starts to decrease. The ratio of the UC green (543 nm) to red emission (656 nm) can be fitted to a cubic equation in terms of the temperature from 306 to 523 K, meaning that this phosphor could be used to sense temperature. In addition, the SrF2 :Yb 3+, Ho 3+ NPs were found to be paramagnetic with magnetization values of 1.32 emu g −1 (at 50 K and H = 15 kOe) and 0.299 emu g −1 (at 300 K and H = 15 kOe), respectively. The magnetization exhibits a good reciprocal response to the temperature from 50 to 300 K, which could open up a new pathway to sense temperature in a low-temperature environment. Due to the good UCL and excellent temperature stability of the SrF2 : 20% Yb 3+, 2% Ho 3+ NPs, the current work shows that this material could be used for temperature sensing from 50 to 523 K, bioimaging and magnetic resonance imaging using a single system.